CO2 Methanation over Supported Ru/Al2O3 Catalysts: Mechanistic Studies by In situ Infrared Spectroscopy. Issue 12 (9th August 2016) - Zheng, Jian; Wang, Chengyang; Chu, Wei; Zhou, Yuanlin; Köhler, Klaus
Abstract: Alumina supported ruthenium particles with an average diameter of 2 nm were prepared by a modified ethylene glycol reduction method. Catalytic methanation of CO2 over this catalyst was studied by in situ FTIR spectroscopy. After pretreatment in H2, different types of adsorbed species were detected on the catalyst surface at 200 °C. Based on a series of targeted experiments under variation of gas composition, order of addition, reaction time and temperature, a reaction scheme and the rate‐determining steps of CO2 methanation are proposed. Two potential reaction paths for the hydrogenation of CO2 to form CH4 were identified: (I) CO adsorbed on the Ru metal surface acted as active intermediate and the CO methanation followed. The dissociation of CO to form surface carbon represents the rate‐determining step. (II) Formyl species formed by hydrogenation of adsorbed CO2 are the active intermediate and the formation of formyl was the rate‐determining step. Abstract : Two reaction paths for CO2 methanation over Ru/Al2 O3 were identified: a) CO acted as the active intermediate for the hydrogenation of by adsorbed H atoms. b) Formyl species formed by reduction of adsorbed CO2 are converted fast to methane by hydrogenation with surface H atoms.